2013
DOI: 10.1371/journal.pone.0060564
|View full text |Cite
|
Sign up to set email alerts
|

Does Herbivorous Fish Protection Really Improve Coral Reef Resilience? A Case Study from New Caledonia (South Pacific)

Abstract: Parts of coral reefs from New Caledonia (South Pacific) were registered at the UNESCO World Heritage list in 2008. Management strategies aiming at preserving the exceptional ecological value of these reefs in the context of climate change are currently being considered. This study evaluates the appropriateness of an exclusive fishing ban of herbivorous fish as a strategy to enhance coral reef resilience to hurricanes and bleaching in the UNESCO-registered areas of New Caledonia. A two-phase approach was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 94 publications
6
28
0
Order By: Relevance
“…Taylor 2014;Williams et al 2015a) in highly dynamic ecosystems such as coral reefs before attributing differences in fish density and biomass to fishing effects alone. Similar to predator-herbivore interactions, we found no significant cascading trophic links between the density of herbivorous fishes and benthic composition (also see Carassou et al 2013). However, we found some regional differences in benthic composition, with CCA on average five times as abundant in the Ribbons, and rubble and sand on average nearly five times as abundant in the Swains.…”
Section: Discussionsupporting
confidence: 63%
“…Taylor 2014;Williams et al 2015a) in highly dynamic ecosystems such as coral reefs before attributing differences in fish density and biomass to fishing effects alone. Similar to predator-herbivore interactions, we found no significant cascading trophic links between the density of herbivorous fishes and benthic composition (also see Carassou et al 2013). However, we found some regional differences in benthic composition, with CCA on average five times as abundant in the Ribbons, and rubble and sand on average nearly five times as abundant in the Swains.…”
Section: Discussionsupporting
confidence: 63%
“…However, the high macroalgae on all habitats in this study did not significantly affect the abundance and biomass of herbivorous fish as suggested by the RDA. Similar results have been found in other studies (Wellington & Victor 1985;Williams 1986;Chabanet & Letourneur 1995;Carassou et al 2013). For example, Abah was dominant on the fronts, where despite the overwhelming dominance of macroalgae, it did not significantly influence the abundance and biomass distribution of this or any other species.…”
Section: Fish and Environmental Variables Associationssupporting
confidence: 90%
“…Similar results have been found in other studies (Wellington & Victor ; Williams ; Chabanet & Letourneur ; Carassou et al . ). For example, Abah was dominant on the fronts, where despite the overwhelming dominance of macroalgae, it did not significantly influence the abundance and biomass distribution of this or any other species.…”
Section: Discussionmentioning
confidence: 97%
“…The one weak association was a negative association between acan thurids and coral cover that would indicate their preference for feeding on dead coral surfaces (Marshell & Mumby 2012). While this does not support some ecosystem management recommendations, it does correspond with a number of large-scale studies that have failed to find significant coral− parrot fish associations, identified other factors, or found that herbivorous fish passively associate with, rather than actively control, algae-coral relationships (McClanahan et al 2011b, Wilson et al 2012, Carassou et al 2013, Russ et al 2015, Suchley et al 2016.…”
Section: Discussionmentioning
confidence: 86%